Free light chains in patients with HIV: establishing local reference ranges and their association with stage of disease, chronic antigen stimulation and the effect of Haart - Germishuys, Jurie J. (Stellenbosch : Stellenbosch University, 2012)
Thesis (MMedSc)--Stellenbosch University, 2012.